2008
DOI: 10.1592/phco.28.7.821
|View full text |Cite
|
Sign up to set email alerts
|

Pharm.D. Pathways to Biomedical Research: The National Institutes of Health Special Conference on Pharmacy Research

Abstract: To address the shortage of research-trained pharmaceutical scientists (or doctor of pharmacy [Pharm.D.] scientists), a 2-day pharmacy research conference titled "Pharm.D. Pathways to Biomedical Research" was convened on December 13-14, 2006, at the National Institutes of Health (NIH) campus (Bethesda, MD). The workshop included invited speakers and participants from academia, industry, and government. Forty-two pharmacy schools were represented, including deans and clinical pharmaceutical scientists with curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 4 publications
(4 reference statements)
0
23
0
Order By: Relevance
“…However, despite a strong foundation to pursue careers as pharmaceutical scientists, the profession may underutilize this opportunity. [1][2][3][4] When pharmacy faculty members who were working in research intensive settings in 2002 were surveyed, only half of the respondents had formal research training. 1 Additionally, the American Association of Colleges of Pharmacy (AACP) reported that only 22 doctor of pharmacy (PharmD)-trained researchers were principal investigators on funded awards from the National Institutes of Health (NIH) in 2008.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite a strong foundation to pursue careers as pharmaceutical scientists, the profession may underutilize this opportunity. [1][2][3][4] When pharmacy faculty members who were working in research intensive settings in 2002 were surveyed, only half of the respondents had formal research training. 1 Additionally, the American Association of Colleges of Pharmacy (AACP) reported that only 22 doctor of pharmacy (PharmD)-trained researchers were principal investigators on funded awards from the National Institutes of Health (NIH) in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although the preferred path for pharmacists to be trained as clinical pharmaceutical scientists has been disputed, it is generally accepted that exposing students to research while pursuing a PharmD degree would be beneficial. In fact, a uniform recommendation from the ACCP White Paper and the NIH conference was to increase students' exposure to research with faculty members early in the PharmD curricula.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathways in Biomedical Research," to discuss training of pharmacy researchers. 3 Included within the conference recommendations was for schools of pharmacy to promote pharmacy research experiences for student pharmacists. 3 As such, it should be beneficial for the curriculum of Doctor of Pharmacy (Pharm.D.)…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…3 Included within the conference recommendations was for schools of pharmacy to promote pharmacy research experiences for student pharmacists. 3 As such, it should be beneficial for the curriculum of Doctor of Pharmacy (Pharm.D.) programs to include a mechanism by which student pharmacists can obtain an understanding of basic science research and its roles in medical and pharmaceutical advancement.…”
Section: Introduction/backgroundmentioning
confidence: 99%